Unveiling the potential of Chinese herbs in combating cervical cancer: Understanding their mechanisms of action and herbal formulations - Priyanka Ray; Diptayan Paul (Elsevier, 2024)
Introduction: Within the framework of Traditional Chinese Medicine (TCM), this study investigates the vast field of Chinese herbal medicine's potential as a powerful weapon in the fight against cervical cancer. Methods: A thorough search was made through Scopus, PubMed, ResearchGate, and Elsevier Journals for future studies on the healing and cervical cancer-fighting properties of Chinese plants and herbal formulations. Result: Scutellaria baicalensis, Curcuma longa, Ganoderma lucidum, Camptotheca acuminata, Antrodia cinnamomea, Terminalia catappa, Chelidonium majus, Lycopodium clavatum, and Myrica cerifera possess cancer-fighting bioactive compounds. Baicalein in Scutellaria baicalensis suppresses cervical cancer growth and alters Notch signaling, while curcumin in Curcuma longa inhibits cell migration, invasion, and HPV oncogenes, also reducing inflammation and protecting cells. Ganoderma lucidum lowers inflammation, boosts the immune system, and blocks JAK/STAT5 signaling, preventing EMT in cervical cancer cells. Camptothecin in Camptotheca acuminata inhibits DNA topoisomerase I, reducing cancer cell growth, with Antrodia cinnamomea controlling apoptosis. Terminalia catappa uses MMP-9 and MAPK to inhibit spread, while Chelidonium majus, Lycopodium clavatum, and Myrica cerifera induce apoptosis and cell cycle arrest. Zhidai Decoction and Guizhi-Fuling-decoction suggest traditional Chinese medicine can treat HPV and cervical cancer. Discussion: Scutellaria baicalensis, Curcuma longa, Ganoderma lucidum, Camptotheca acuminata, Antrodia cinnamomea, Terminalia catappa, Chelidonium majus, Lycopodium clavatum, and Myrica cerifera possess bioactive substances effective against cancer. They work through mechanisms like inhibiting cell growth, altering signaling pathways, and inducing apoptosis. Traditional Chinese medicine formulations like Zhidai Decoction and Guizhi-Fuling-decoction show potential in treating HPV and cervical cancer.